Inflammatory fibroid polyp - a cause of small bowel obstruction. (November 2017) - Al-Droubi, Hiam; Lal, Neeraj; Najam, Hussain; Khan, Shahzad; Marzook, Himaz; Waraich, Naseem; McBride, Sam
Abstract : Introduction: Inflammatory fibroid polyps (IFPs) are rare, benign tumours originating from the submucosa of stomach or small bowel. They account for only 0.1-3.0% of all gastric polyps. Histogenesis remains unknown. In adults, benign tumours such as IFPs are an uncommon cause of small bowel obstruction. Case description: A 54 year old male patient with known hypertension presented to the emergency department with a 24 hour history of sudden onset and severe right iliac fossa pain, which progressively worsened. He was pyrexial on admission, had decreased appetite and had significant weight loss over the previous few months. There were no other gastrointestinal symptoms. The clinical examination and laboratory findings were consistent with a diagnosis of appendicitis. However, a CT scan of the abdomen and pelvis was suggestive of small bowel obstruction. This scan was reported by two radiologists due to the inconclusive aetiology of the small bowel obstruction. Though the first impression was acute-on-chronic crohn's disease, on further analysis of the images a well defined oval shaped homogenous mass was noted in the distal ileum. An MRI scan confirmed terminal ileal inflammatory changes with intraluminal cystic changes. The patient underwent a laparoscopic right hemicolectomy. Intraoperatively, a cystic mass in the terminal ileum was found to be causing small bowel obstruction. Histology revealed that the mass was composed of fusiform and stellate shaped stromal cells with marked oedema and eosinophilia consistent with the diagnosis of IFP. The patient had an uneventful postoperative recovery. Results and Conclusions: Despite the fact that inflammatory fibroid polyps are very rare lesions, they should be taken into consideration as a differential diagnosis in patients presenting with small bowel obstruction, as prompt surgical resection is the only known effective treatment.